Antidepressant use and interpersonal violence perpetration: a protocol for a systematic review and meta-analysis. Issue 1 (13th January 2021) - Keen, Claire; Foulds, James A; Willoughby, Melissa; Newton-Howes, Giles; Knight, Josh; Fazel, Seena; Borschmann, Rohan; Kinner, Stuart A; Young, Jesse T
Abstract : Introduction: There are conflicting perspectives as to whether antidepressant medication increases, decreases or has no effect on violence perpetration, impulsivity and aggressive behaviour. This is an important question given the widespread use of antidepressant medication and the significant medical, social, legal and health consequences of violence. We aim to: (1) systematically identify observational studies and randomised controlled trials that quantify the relationship between antidepressant use and interpersonal violence; (2) assess the quality of studies that quantify the relationship between antidepressant use and interpersonal violence and (3) estimate the pooled prevalence and measure of effect for the relationship between antidepressant use and interpersonal violence. Methods and analysis: We will search MEDLINE, EMBASE, CINAHL, PsycINFO, PubMed and the Cochrane Library for relevant peer-reviewed literature. Our primary outcome is the perpetration of violent acts directed at others. Our secondary outcome is physical, interpersonal aggression measured through validated surveys. We will include randomised controlled trials, cohort studies and case–control studies that examine the association between the use of antidepressants and violence perpetration and/or physical aggression. No restrictions will be placed on the population. We will use the Methodological Standard for Epidemiological Research scale to assess the quality of included studies. We will provide an overview of the included studies and assess heterogeneity and publication bias. If there are sufficient studies, we will conduct meta-analyses to examine the possible association between antidepressants and violence, and undertake meta-regression to examine the effect of antidepressant class, length of follow-up, age of participants and population subgroups on the association between antidepressants and violence. Ethics and dissemination: No ethics approval is required. Our findings will be disseminated through a peer-reviewed journal article and conference presentations. PROSPERO registration details: CRD42020175474.